Fuzzy Logic Approach for Measuring Graduate Attributes in Outcome-Based Education for Electronics - Sutoto, Yuli Sutoto (Journal of Intelligent System and Telecommunication, 2024)
Outcome-Based Education (OBE) has been adopted by universities in various countries, posing challenges in measuring the achievement of Graduate Attributes (GA) within individual courses and integrating them across study programs. This research employs Fuzzy Logic to assess GA achievement in the Computer Application in Electronics course. The study utilizes the Fuzzy Mamdani method to evaluate several GAs, considering cognitive, psychomotor, and affective domains. The system's input consists of assessments based on Course Learning Outcomes (CLOs), while the output reflects student performance. Experimental results indicate that parameter selection significantly impacts outcomes, though the differences between centroid and bisector fuzzification methods are relatively small, making both viable options. Specifically, the range of GA 7's final value difference using the centroid method falls between -1.9 and 0. In contrast, the bisector method ranges from -1 to 1.9, with a maximum point difference of 1.5 when comparing manual and centroid methods for GA 8. The average value differences are 0.598 for the centroid method and 0.580 for the bisector method.